Educação conectada e fluência tecnológico-pedagógica (FTP) na formação continuada de professores da educação básica no município de Cachoeira do Sul/RS - Hesse, Rafaela (2022)
The following Master Thesis main objective was to analyze whether the actions promoted by the PIEC and the BNDES Initiative, as well as the emergency training actions, expanded on an emergency basis during remote and/or hybrid education, promoted the development of the teaching Technological and Pedagogical Fluency of education professionals in the municipality of Cachoeira do Sul/RS. The specific objectives were: a) to discuss the integration of educational technologies in the education/training of basic education teachers, based on the construction of the State of knowledge; b) to analyze the repercussion of the actions promoted by the BNDES Initiative and the emergency training carried out during the pandemic on the development of the Technological and Pedagogical Fluency of teachers and managers of basic education in the municipality of Cachoeira do Sul/RS; c) to manufacture audiovisual material from the recording of testimonials and teaching experiences in progress as a record and memory of technological-pedagogical initiatives in the context of remote education. The research was of a qualitative character, with a Design-Based Research methodological approach; data analysis was carried out based on the construction of three cartographic matrices: the DialogicalProblematizing Matrix, the Thematic-Organizing Matrix and the Thematic-Analytic Matrix. To obtain the data produced, a survey questionnaire and the recording of memories were used. As final considerations, it should be noted that, in the case of Cachoeira do Sul/RS, the Department of Education was concerned with assisting teachers in the challenges encountered for the integration of technologies in pedagogical practices. Electronic equipment was acquired and experiences were shared among teachers, as well as the exchange of experiences among teachers. Despite this, one can see that such actions were not enough for the integration of technologies to become a reality in the network. Likewise, public policies were not sufficient or were not consistent with the different contextual realities of the municipality. The need for public policies, articulated with the context and the needs of schools, as well as the training needs of teachers, is highlighted. Training that contributes to the development of teachers' Technological and Pedagogical Fluency, more solid and critical training that will qualify teaching practices.